TECHNOFLOW AMONG SPANISH AND SWEDISH STUDENTS: A CONFIRMATORY FACTOR MULTIGROUP ANALYSIS - Rodríguez Sánchez, Alma María; Cifre Gallego, Eva; Salanova Soria, Marisa; Aborg, Carl (Anales de Psicología / Annals of Psychology, 2008)
Despite the relevance of flow in recent research in Positive Psychology, there exist few studies on this optimal experience in technology settings. The aim of this study is to confirm the three-factorial (enjoyment, absorption and intrinsic interest) structure of technoflow. 154 university students who use computers in their studies (N=78 Spanish students and N=76 Swedish students) answered a questionnaire. Confirmatory Factor Analyses showed a better adjustment of a bifactorial model of technoflow (enjoyment and absorption). Multigroup Analyses showed that the model is invariant across samples. Practical and theoretical implications as well as future research are also discussed.